2017
DOI: 10.1038/s41467-017-00457-z
|View full text |Cite
|
Sign up to set email alerts
|

Modular fluorescence complementation sensors for live cell detection of epigenetic signals at endogenous genomic sites

Abstract: Investigation of the fundamental role of epigenetic processes requires methods for the locus-specific detection of epigenetic modifications in living cells. Here, we address this urgent demand by developing four modular fluorescence complementation-based epigenetic biosensors for live-cell microscopy applications. These tools combine engineered DNA-binding proteins with domains recognizing defined epigenetic marks, both fused to non-fluorescent fragments of a fluorescent protein. The presence of the epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 69 publications
1
59
0
Order By: Relevance
“…Live-cell reporters of histone H3 55 and H4 56 lysine acetylation have also been developed. More recently, a fluorescence complementation sensor has been used for real-time visualization of DNA methylation and H3K9me3 marks at major satellite repeats 57 . It will be exciting to apply these reporters to the tracking of the long-term inheritance of these epigenetic marks in live cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Live-cell reporters of histone H3 55 and H4 56 lysine acetylation have also been developed. More recently, a fluorescence complementation sensor has been used for real-time visualization of DNA methylation and H3K9me3 marks at major satellite repeats 57 . It will be exciting to apply these reporters to the tracking of the long-term inheritance of these epigenetic marks in live cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In the case of ZFP57, selectivites for hmC and caC have been engineered . ZFP and other customizable DNA binding domains have also been combined with MBD for the detection of mC in DNA via signalling with split fluorescent proteins…”
Section: Design Of Protein Scaffolds With Selectivity For Oxidized MCmentioning
confidence: 99%
“…In the case of ZFP57, selectivites for hmC and caC have been engineered. [73] ZFP and other customizable DNA binding domains have also been combined with MBD for the detection of mC in DNA via signalling with split fluorescent proteins [111][112][113] Later, transcription-activator-like effectors (TALEs) have been discovered as alternatives to ZFP that feature a more simple and programmable binding mode. [114,115] TALEs bear a central domain consisting of concatenated repeats that each however recognize only one instead of three nucleobases, which reduces the number of required repeats to target any DNA sequence from 64 to only four ( Figure 5A and B show structural overviews).…”
Section: Scaffolds With Programmable Sequence Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In particular, uorescence sensors with modied uorophores, which are based on deoxyribonucleic acid (DNA), appear to be promising for application due to their stability, high specicity, and sensitivity. 3,4 Fluorescence sensors to detect the presence of a target molecule are typically based on the uorescence resonance energy transfer (FRET) process, 5 thus the choice of the receptor pair usually determines the analytical performance of the uorescence sensor. 6 To reduce the limitations that characterize the receptor pairs, studies have shown that novel nanomaterials, which exhibit an effective quenching ability in a broad range of emission wavelengths, can be used as broad-spectrum quenching molecules.…”
Section: Introductionmentioning
confidence: 99%